Bone taphonomy of the Schöningen "Spear Horizon South" and its implications for site formation and hominin meat provisioning. Issue 89 (December 2015) - Starkovich, Britt M.; Conard, Nicholas J.
Abstract: This paper presents the faunal remains from the new excavation area at the Lower Paleolithic site of Schöningen. The focus of the study is on the southern extension of the main find horizon (Spear Horizon South), which includes the layer that yielded the famous Schöningen spears (13 II-4). Taxonomic data corroborate previous studies, that hominins primarily hunted Equus mosbachensis, a large Pleistocene horse. Equid body part representation at the site suggests that the animals were hunted and butchered locally. There is no evidence for density-mediated attrition in the assemblage. Weathering damage is uncommon, though there is ample evidence that carnivores had access to the bone. Carnivore bite sizes were measured and compared to experimental data provided by previous authors. Based on relationships between bite size and carnivore behavior and body size, we conclude that the primary modifying agents were large carnivores (i.e., wolves or saber-toothed cats). Previous studies show that carnivores often had secondary access to the remains, after hominins. Cut marks are commonly arranged haphazardly on the bones. This may indicate that multiple hominins participated in the butchery of horse skeletons, or that they were butchered over the course of hours or days. Cut marks on axial elements are more "orderly, " which probably reflects the physical logistics of orienting one's body in relation to a large carcass. These data differ from sites formed by Middle and Upper Paleolithic hominins, which might suggest that in later times, a system of organized meat provisioning was already in place. Taken together, the faunal evidence from the Spear Horizon South indicates that late Lower Paleolithic hominins using the site understood the behaviors of different prey species, hunted socially to take down large game, and successfully competed with large carnivores on the landscape for primary access to ungulate remains.